Association of low-density lipoprotein cholesterol within the normal range and NAFLD in the non-obese Chinese population: a cross-sectional and longitudinal study. Issue 12 (7th December 2016) - Sun, Dan-Qin; Wu, Sheng-Jie; Liu, Wen-Yue; Wang, Li-Ren; Chen, Yi-Ran; Zhang, Dong-Chu; Braddock, Martin; Shi, Ke-Qing; Song, Dan; Zheng, Ming-Hua
Abstract : Objectives: The relationship between normal low-density lipoprotein cholesterol (LDL-c) levels and non-alcoholic fatty liver disease (NAFLD) in non-obese individuals remains unclear. We aimed to investigate the precise prevalence and incidence of NAFLD within the normal LDL-c range in non-obese individuals. Design: Cross-sectional and longitudinal study. Setting: Wenzhou Medical Center of Wenzhou People's Hospital from 2010 to 2014. Participants: 183 903 non-obese individuals were enrolled from a cross-sectional population, and a total of 16 173 initially NAFLD-free non-obese individuals were included who completed a 5-year follow-up examination in the longitudinal population. Results: In our study, NAFLD was defined by ultrasonographic detection of steatosis in the absence of other liver disease. The cross-sectional study showed that at baseline, the prevalence of NAFLD was 13.9% in non-obese individuals with normal LDL-c levels. The prospective study demonstrated that NAFLD-free participants developed NAFLD during the 5-year follow-up period, with a cumulative incidence of 14.4%. In addition, the ORs for NAFLD in the cross-sectional population were 1.11 (95% CI 1.04 to 1.18), 1.37 (95% CI 1.27 to 1.47) and 1.56 (95% CI 1.43 to 1.69), respectively, after adjusting for known confounding variables. The HRs for NAFLD in the longitudinal population were 1.15 (95% CI 0.98 to 1.36), 1.32 (95% CI 1.10 to 1.58) and 1.82 (95% CI 1.47 to 2.52), compared with Q1. Individuals with higher LDL-c level within the normal range had an increased cumulative incidence rate of NAFLD in non-obese individuals. Conclusions: NAFLD is prevalent in the non-obese Chinese population. Furthermore, this is the first study to demonstrate that increased normal LDL-c levels are independently associated with an elevated risk of NAFLD in non-obese individuals.